Beyond onboard sensors in robotic swarms: Local collective sensing through situated communication - Rodrigues, T. (2015)
The constituent robots in swarm robotics systems are typically equipped with relatively simple, onboard sensors of limited quality and range. When robots have the capacity to communicate with one another, communication has so far been exclusively used for coordination. In this paper, we present a novel approach in which local, situated communication is leveraged to overcome the sensory limitations of the individual robots. In our approach, robots share sensory inputs with neighboring robots, thereby effectively extending each other’s sensory capabilities. We evaluate our approach in a series of experiments in which we evolve controllers for robots to capture mobile preys. We compare the performance of (i) swarms that use our approach, (ii) swarms in which robots use only their limited onboard sensors, and (iii) swarms in which robots are equipped with ideal sensors that provide extended sensory capabilities without the need for communication. Our results show that swarms in which local communication is used to extend the sensory capabilities of the individual robots outperform swarms in which only onboard sensors are used. Our results also show that in certain experimental configurations, the performance of swarms using our approach is close to the performance of swarms with ideal sensors.